2004
DOI: 10.2134/agronj2004.2470
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Herbicide‐Resistant Corn Technology in a Kura Clover Living Mulch System

Abstract: Previous research has shown that with adequate suppression, kura clover (Trifolium ambiguum M. Bieb.) can be managed as a living mulch in corn (Zea mays L.); however, significant yield loss was observed in some environments. This study evaluated two herbicide‐resistant corn hybrids at three levels of kura clover living mulch suppression over multiple environments. In 1999 and 2000 near Arlington and in 2000 near Lancaster, WI, glyphosate [N‐(phosphonomethyl)glycine]‐resistant corn (Roundup Ready corn, RRC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Individual plots measured 3 by 12 m and each treatment combination had four replications. Row establishment treatments included rotary zone tillage (RZT), shank striptillage (ST), and banded herbicides (BH), and were chosen based on previous work and their practicality for farmers managing a KCLM (Affeldt et al, 2004;Alexander et al, 2019a). Additional details regarding the row establishment treatments are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual plots measured 3 by 12 m and each treatment combination had four replications. Row establishment treatments included rotary zone tillage (RZT), shank striptillage (ST), and banded herbicides (BH), and were chosen based on previous work and their practicality for farmers managing a KCLM (Affeldt et al, 2004;Alexander et al, 2019a). Additional details regarding the row establishment treatments are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the early work with KCLM systems utilized herbicides (Albrecht & Sabalzagaray, 2006;Zemenchik et al, 2000). Affeldt et al (2004) utilized broadcast glyphosate and dicamba and banded dicamba and clopyralid before planting to chemically suppress kura clover in the row and interrow zones. This suppression regime resulted in no difference between maize yield in monocrop and KCLM treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is likely that legume LM alone will not provide sufficient N necessary for optimum productivity in corn [19]. The authors of [20] applied N at 45 kg/ha between the V3 and V5 stages to avoid resource limitation for corn growth, and the authors of [21] observed that side dressing N to LM grown with corn increased the whole-plant corn yield.…”
Section: Introductionmentioning
confidence: 99%